Characterization of acid mine drainage sources in the Iberian Pyrite Belt : base methodology for quantifying affected areas and for environmental management - Grande, J. A. (2014)
The present work aims to propose a method- ology for quantifying the sources of acid mine drainage (AMD) and to characterize the magnitude of the affected areas in the Iberian Pyrite Belt (SW Spain). Such an approach allows the creation of a support tool for managing land and natural resources valorization, which may be easily applied in similar mining regions. The motivation and usefulness of this work can be realized by focusing on two main emerging strategic issues: (1) water resources management, with the example of Alcolea dam that will receive water from affected areas in the Iberian Pyrite Belt; and (2) mineral resources valorization, especially, regarding copper exploration due to increasing market prices. The used methodology included the following general steps: it started with an inventory of the mines in the Iberian Pyrite Belt, followed by ﬁeld cartography campaigns and ﬁnally the quantiﬁcation of affected areas and contaminant discharges. The results of the present work serve to conﬁrm and quantify the magnitude of the AMD pollution in the Pyrite Belt. A total affected area of about 4,847 ha was estimated. Taking into account this ﬁgure and combining it with the annual average precipitation (650 L/m2) results in an estimation of 31,503,680 m3/year of discharging water affected by the presence of sulphides. In this scenario, a total annual contribution of 260,056 tonnes/year was obtained for sulphates, which means more than 712 tonnes a day. In the case of arsenic, a toxic element, the total annual contribution is more than 20 tonnes, or close to 55 kg/day. Regarding copper, this economically interesting metal translates into total contributions of 10,364 tonnes/ year in the generating medium. This gave more than 28 tonnes/day, which today sits at 8,200 dollars/tonne. This result suggests that solutions aimed at recovering this resource should be searched. It may represent a ﬁnancial return at the same time that it would mean overcome environmental liabilities.